2010
DOI: 10.1590/s1516-89132010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among Brazilian soybean cultivars based on SSR loci and pedigree data

Abstract: In this study, simple sequence repeats (SSR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
2
22
0
3
Order By: Relevance
“…High levels of polymorphism were revealed in soybean by the use of neutral SSR markers, for both the number of alleles per locus and gene diversity (Akkaya et al, 1992;Narvel et al, 2000;Priolli et al, 2002;Priolli et al, 2010). In this study, using SSR markers and considering the parameters of BNF and protein content, we have also observed high variability amongst both modern germoplasms cultivated in Brazil and ancestral lines.…”
Section: Discussionsupporting
confidence: 56%
“…High levels of polymorphism were revealed in soybean by the use of neutral SSR markers, for both the number of alleles per locus and gene diversity (Akkaya et al, 1992;Narvel et al, 2000;Priolli et al, 2002;Priolli et al, 2010). In this study, using SSR markers and considering the parameters of BNF and protein content, we have also observed high variability amongst both modern germoplasms cultivated in Brazil and ancestral lines.…”
Section: Discussionsupporting
confidence: 56%
“…Bonato et al (2006) observed that the dendrogram obtained with AFLP markers was consistent with the pedigree of soybean genotypes analyzed. Priolli et al (2010) found that the clustering of 168 soybean cultivars obtained by UPGMA method, based on the information of SSR markers, were consistent with ancestors which are common among cultivars within the same group.…”
Section: Diversity Based On Molecular Markersmentioning
confidence: 58%
“…Despite the high number, the Brazilian soybean cultivars are extremely uniforms because they originated from only a few ancestral lines, which resulted in a narrow genetic base of germplasm (Miranda et al, 2007;Priolli et al, 2010;Wysmierski and Vello, 2013). This fact, together with the lack of genetic variability, brings risks for cultivars productivity levels and susceptibility to pests, pathogens and environmental stresses.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…Vieira et al (2009) observed similarities between 0.27 and 0.98 and average similarity of 0.53 in another group of 53 genotypes. Other 168 cultivars showed similarity indices between 0.01 and 0.9 and average similarity of 0.42 (Priolli et al, 2010). Therefore, the low values of effective size, the high estimates of relatedness, and the elevated similarity indices indicate a high similarity in the improved cultivars.…”
Section: Introductionmentioning
confidence: 95%